PSYCHOLOGICAL AND PEDAGOGICAL CONDITIONS OF IMPROVEMENT OF PROFESSIONALISATION PROCESSES OF MASTER`S DEGREE STUDENTS OF NATIONAL ACADEMY OF THE NATIONAL GUARD OF UKRAINE - Pasichnyk, V.; Bielai, S.; Kernickii, O. (Honor and Law, 2020)
The article presents the results of theoretical and empirical studies of the peculiarities of the process of professionalization of Master degree students of the National Academy of the National Guard of Ukraine in the specialization "Moral and psychological support of the activity of military units and connections of the National Guard of Ukraine" of the second (Master’s) level of higher education. Based on the results of the theoretical research, the relevance of revealing the psychological and pedagogical conditions for improving the professionalization of the studied Master`s degree students is substantiated, the essence and content of professionalization of the specialist as a process of professional formation of the subject of labor, part of the ontogeny of a person from the beginning of the formation of his professional activity are determined. As well as the movement of the individual in the space and time of professional work. It is established that professionalization is the individual development of professionally significant qualities and abilities, professional knowledge and skills, active qualitative transformation of the person of his inner world, which leads to a fundamentally new state and way of life - creative self-realization in the profession. Professional development depends on the features of the activity, the individual capabilities of a particular personality and the conditions of professionalization. The results of the empirical researches on the evaluation of the current state of professional training of Master`s degree students at NAU and the main existing problems of the process of their professionalization are revealed. According to the results of the researches, the psychological and pedagogical conditions for improving the process of professionalization of the mentioned Master`s degree students, which are first presented in a systematic and holistic form, are substantiated. They are the basis for the implementation of current innovations in the context of reforming the moral and psychological support of the activities of NSU formations and the transition to NATO standards.